Previdência para as mulheres no Brasil: Reflexos da inserç\~ao no mercado de trabalho - Milko Matijascic (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Among occupied women, the proportion of those who contribute to the public pension system was greater than for man in 2014, representing a new scenario for Brazil. The insertion of women among benefits that required a higher density of contribution raised and is reflected by a higher proportion among length of contribution pensions and a smaller one for survivor benefits, since the male breadwinner model looses ground and new family arrangements are present. Temporary benefits present a higher women incidence since they are more conscious about their situation and suffer bigger pressures to conciliate family duties and professional obligations that affect her health condition. This scenario shows that the option to emphasize cash transfer in detriment to social services may create serious constraints for Brazilian women.
Keywords: I39; 330; social security; gender; social policies